2017
DOI: 10.1590/2317-1782/20172016238
|View full text |Cite
|
Sign up to set email alerts
|

Alterações retrococleares na esclerose sistêmica: relato de casos

Abstract: Purpose: To report three cases of patients with Systemic Sclerosis (SSc) and retrocochlear impairments. Methods: This is a case report of three individuals with SSc and retrocochlear impairments assisted at a rheumatology outpatient clinic. All individuals underwent Brainstem Auditory Evoked Potential (BAEP) and, when necessary, audiometry. Results: All three individuals presented sensorineural hearing loss. Although no retrocochlear impairment was identified in the basic audiologic evaluation, the BAEP result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…On the audiometric testing, bilateral sensorineural hearing loss is the most common finding followed by mixed hearing loss. 24 These audiometric features are consistent with our findings of decreased spiral ganglion neurons in the cases of scleroderma. We also report vascular involvement of the stria vascularis in the lower basal cochlear turns, which is consistent with lesions reported in other vasculitides such as granulomatosis with polyangiitis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…On the audiometric testing, bilateral sensorineural hearing loss is the most common finding followed by mixed hearing loss. 24 These audiometric features are consistent with our findings of decreased spiral ganglion neurons in the cases of scleroderma. We also report vascular involvement of the stria vascularis in the lower basal cochlear turns, which is consistent with lesions reported in other vasculitides such as granulomatosis with polyangiitis.…”
Section: Discussionsupporting
confidence: 92%
“…Both patients in this study reported hearing loss and one reported tinnitus. On the audiometric testing, bilateral sensorineural hearing loss is the most common finding followed by mixed hearing loss 24 . These audiometric features are consistent with our findings of decreased spiral ganglion neurons in the cases of scleroderma.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, some authors found a wide variety of audiogram configurations in their studies ( 5 ). In few cases ( 13 15 ) sensorineural hearing loss was related to vestibulocochlear nerve neuropathy. In a small percentage of tested patients ( 3 , 6 , 8 , 10 , 16 , 17 ), usually not more than few percent, mixed or conductive hearing loss was described, though auditory tube disorders or tympanometry abnormalities were observed much more frequently ( 6 , 8 ) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%